The Power of Images: Exploring Gender Performances of Filipino Female Celebrities on Instagram - Sumaylo, Reynes Lastimoza (Eximia, 2023)
Instagram is a social photography ‘app’ designed to run on a Smartphone through which the social media user can produce visual and textual impressions, thus allowing the ambient viewer to interact and distribute these impressions (Mirsarraf et al., 2017). This study aimed to examined how social media networks are changing the way female celebrities portray themselves to the public and how these digital platforms are assisting in the cultivation of celebrity personas. This study was analyzed using feminist theory, and framing analysis. The results revealed that each female celebrity used Instagram in different ways; however, there were commonalities to their self-representation. Anne Curtis Smith, Liza Soberano, and Kathryn Bernardo all used the medium as more or less a self-promotion tool. Anne Curtis Smith created a somewhat accessible persona, though this was done through self-objectifying, body centric, and sexually explicit images and messaging; Liza Soberano created an accessible persona through less objectifying visual messaging; and Kathryn Bernardo created a dynamic and distant persona through sexualized and dream-like imagery and subject matter.